What drives the dynamics of a soil mite population under seasonal flooding? A null model analysis - Pequeno, Pedro Aurélio Costa Lima; Franklin, E. (Experimental and Applied Acarology, 2014)
Floods can inflict high mortality on terrestrial organisms, but may also promote adaptive evolution. In seasonal floodplains, several taxa show flood-related traits that may be important for their long-term persistence, but the available evidence is conflicting. Here, we used a simulation approach to investigate the interplay between seasonal floods and submersion resistance in driving the population dynamics of the parthenogenetic soil mite Rostrozetes ovulum in an Amazonian blackwater floodplain. First, we gathered data from two flood cycles to estimate field survival rate. Next, we used further data from a submersion survival laboratory experiment and a historical flood record to build a null model for R. ovulum's survival rate under seasonal flooding, and then tested it against field survival estimates. Floods caused marked density declines, but the two estimates of field survival rate were statistically equivalent, suggesting relatively constant survival across years. Submersion survival time varied tenfold among individuals, but its variability was within the range known for life history traits of other asexual invertebrates. Both field survival rates were consistent with the null model, supporting seasonal flooding as the main mortality factor. Surprisingly, though, average flood duration was actually larger than the average mite could survive, suggesting that population persistence relies on relatively rare, super-resistant phenotypes. Overall, the studied R. ovulum population appears to have a mainly density-independent dynamics across years, with its viability depending on mechanisms that buffer flood survival rate against temporal oscillations. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Abundance; Reproduction, Asexual; Disturbance; Flooding; Floodplain; Life History Trait; Mite; Mortality; Numerical Model; Seasonality; Soil Fauna; Survival; Amazonia; Acari; Haplozetidae; Invertebrata; Rostrozetes; Animals; Flooding; Mite; Parasitology; Population Dynamics; Season; Soil; Animal; Floods; Mites; Population Dynamics; Seasons; Soil